Litsea cubeba Essential Oil Yield Harvested from Different Habitat Types on Mt. Papandayan, West Java, Indonesia - Ichsan Suwandhi; Cecep Kusmana; Ani Suryani; Tatang Tiryana (Journal of Mathematical and Fundamental Sciences, 2014)
The objective of this research was to determine the yield and chemical composition of Litsea cubeba essential oil harvested from different habitat types on Mount Papandayan, West Java, Indonesia. The methods used were determination of sample plots at each habitat, followed by laboratory testing. Leaf samples were taken from each plot, the oil was extracted in the laboratory using steam distillation, which was subsequently analyzed by GC-MS. The results showed that the yield of essential oil was high (2.76-9.33%). The three dominant chemical compounds found were eucalyptol (16.97-55.78%), α-terpinenyl acetate (7.27-20.44%), and sabinene (14.45-68.05%). The results confirmed the expectation that Litsea cubeba essential oils extracted from Litsea cubeba trees growing in various habitats on Mount Papandayan would show a variety in yield and chemical composition.